Soft palate perforation from Glidescope® intubation: A case report. Issue 9 (24th September 2021) - Oh, Matthew W.; Yarmosh, Alla; Francis, David; Moon, Tiffany S.
Abstract: We highlight a potential major complication from GlideScope intubation—perforation of the soft palate. With increasing use of video laryngoscopy, precautions must be taken to ensure that its continued use does not increase airway complications. Abstract : We highlight a potential major complication from GlideScope intubation—perforation of the soft palate. With increasing use of video laryngoscopy, precautions must be taken to ensure that its continued use does not increase airway complications.